Misinterpretation of Section 304A IPC vis-a-vis 304IPC in medical Negligence cases – Deliberate or Inadvertent? - Binay Kuma; Avinash Kumar; Vinita Kumari; Ashok Rastogi; Himanshi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Negligence is specific tort and in any given circumstances is the failure to exercise that care which the circumstances demand. What amounts to negligence depends on the facts of each particular case. The degree of care required in a particular case depends upon the surrounding circumstances, and may vary according to the amount of risk to be encountered and to the magnitude of the prospective injury. A basic knowledge of how judicial forums deal with the cases relating to medical negligence is of absolute necessity for doctors. The need for such knowledge is more now than before. In light of higher premium being placed by the Indian Forums on the value of human life and suffering, but sometimes misinterpretations are done deliberately or inadvertently when the doctors are charged for culpable homicide not amounting to murder (304 IPC) instead of medical negligence (304 A IPC). A case of medical negligence is being discussed in which a gynaecologist has been charged for 304IPC instead of 304A IPC. The scenario was that, the patient died after readmission in private hospital, who had delivered a healthy baby, managed properly and discharged by the Gynaecologist and suffered undiagnosed complications after discharge at home. The charge was framed that the doctor was absent from the hospital and the case was handled by nurses on telephonic conversation with doctor. Earlier also the doctors had been prosecuted under 304IPC instead of 304A IPC in lower courts and even high courts (e.g. Jacob Mathews V. State of Punjab, Dr. Suresh Gupta V. Govt. of NCT Delhi). But in many cases, finally Supreme Court set aside the judgement of high court and held that the doctors could not be criminally prosecuted.